Effect of transglutaminase on fresh cheese quality propertises using citric acid as a coagulant - Pham , Thi Hoan; Khanh , Son Trinh (Journal of Technical Education Science, 2021)
The purpose of this study was to evaluate the effect of microbial transglutaminase (MTGase) on cheese quality properties using citric acid as a coagulant agent. The experimental results showed that citric acid has a temperature-dependent ability to agglomerate milk proteins. The process of protein coagulation at 50°C by citric acid (2.0%) gave fresh cheese with yield production (% H), dry matter content (% TS) and cheese solids yield (CSY) of 12.81%, 41.17%, 38.73%, respectively. The reconstituted milk was incubated with MTGase under different conditions of enzyme concentration (0-6.0 IU / g protein), processing temperature (30-50 °C) and time (60-180 min.). Enzyme treatment at 37 °C with enzyme concentration of 2 IU/g protein for 2 hrs showed the highest values of yield (15.03%), dry matter content (46.96%) and cheese solids yield (46.83%). Analytical results of the sensory score, acidity, whey separation and color difference of fresh cheese samples during storage (28 days) showed that using MTGase better maintained the quality of the product. Furthermore, MTGase also improved water holding capacity (reduced whey separation) during storage and did not affect the color of fresh cheese products. Moreover, the physicochemical and microbiological parameters of the product were also determined. The results showed that the quality of fresh cheese coagulated by citric acid met CODEX STAN 221-2001 for unripened cheese including fresh cheese.